Motivating Black males to achieve in school & in life - Kafele, Baruti K. (Alexandria, VA : ASCD, 2009)
Describes strategies teachers may use to help young African-American males succeed in school by instilling them with self-worth.
Introduction -- Learning about Black male students to meet their classroom needs -- Learning about yourself to meet your Black male students' needs -- Three crises -- "Who am I?" -- Developing a young men's empowerment program -- Conclusion.
Includes bibliographical references (p. 107-109).
Professional
Keywords: Academic achievement -- United States; African American boys -- Social conditions; African American men -- Education; African American young men -- Education; African American young men -- Social conditions; Academic achievement -- United States; African American boys -- Social conditions; African American men -- Education; African American young men -- Education; African American young men -- Social conditions